Transition from child to adult health services for young people with cerebral palsy in Ireland: a mixed-methods study protocol. Issue 12 (22nd December 2020) - Ryan, Jennifer M; Fortune, Jennifer; Walsh, Aisling; Norris, Meriel; Kerr, C; Hensey, Owen; Kroll, Thilo; Lavelle, Grace; Owens, Mary; Byrne, M; Walsh, Michael
Abstract : Introduction: The transition from child to adult health services is a challenging and complex process for young people with cerebral palsy (CP). Poorly managed transition is associated with deterioration in health, increased hospitalisations and reduced quality of life. While international research identifies key practices that can improve the experience and outcomes of transition, there is a paucity of data in the Irish context. This research study aims to gain an insight into the experience of transition for young people with CP in Ireland. Methods and analysis: A convergent parallel mixed-methods design will be used to collect, analyse and interpret quantitative and qualitative data. Participants will be young people aged 16–22 years with CP, their parent(s)/carer(s) and service providers. Quantitative and qualitative data will be collected through questionnaires and interviews, respectively. Quantitative data will be reported using descriptive statistics. Where sufficient data are collected, we will examine associations between the experience of transition practices and sociodemographic and CP-related factors, respectively, using appropriate regression models. Associations between service provider characteristics and provision of key transition practices may also be explored using appropriate regression models. Qualitative data will be analysed using the Framework Method. A coding matrix based on key transitional practices identified from the literature will be used to identify convergence and divergence across study components at the integration stage. Ethics and dissemination: The study has been approved by the RCSI University of Medicine and Health Sciences Research Ethics Committee (REC201911010). Results will be presented to non-academic stakeholders through a variety of knowledge translation activities. Results will be published in open access, peer-reviewed journals and presented at national and international scientific conferences.